2016
DOI: 10.1007/s40291-016-0207-2
|View full text |Cite
|
Sign up to set email alerts
|

Semiconductor Whole Exome Sequencing for the Identification of Genetic Variants in Colombian Patients Clinically Diagnosed with Long QT Syndrome

Abstract: Standardized WES assays can be easily implemented, often at a lower cost than sequencing panels. Our results show that WES can identify LQTS-causing mutations and permits differential diagnosis of related conditions in a real-world clinical setting. However, high heterogeneity in sequencing depth and low coverage in the most relevant genes is expected to be associated with reduced analytical sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
2
0
1
Order By: Relevance
“…Para realizar el análisis molecular del caso índice, en Colombia, podemos contar con la secuenciación del exoma/genoma 7 , secuenciación de un panel de genes o un gen individual, el exoma trío, o PCR (Reacción en cadena de la polimerasa) y secuencia del fragmento donde se encuentra la mutación 8 . Como las enfermedades cardiovasculares no son enfermedades clásicas mendelianas, y varias son poligénicas, es difícil tomar una decisión sobre cual gen estudiar, por lo no se recomienda la realización de secuenciación de un solo gen 8 , los paneles de genes o la secuenciación del exoma son opciones válidas, útiles 9 . Si ya se tiene el diagnóstico molecular en el caso índice, se puede utilizar la PCR de la mutación en los familiares de primer grado o con sospecha de estar afectados.…”
Section: Discussionunclassified
“…Para realizar el análisis molecular del caso índice, en Colombia, podemos contar con la secuenciación del exoma/genoma 7 , secuenciación de un panel de genes o un gen individual, el exoma trío, o PCR (Reacción en cadena de la polimerasa) y secuencia del fragmento donde se encuentra la mutación 8 . Como las enfermedades cardiovasculares no son enfermedades clásicas mendelianas, y varias son poligénicas, es difícil tomar una decisión sobre cual gen estudiar, por lo no se recomienda la realización de secuenciación de un solo gen 8 , los paneles de genes o la secuenciación del exoma son opciones válidas, útiles 9 . Si ya se tiene el diagnóstico molecular en el caso índice, se puede utilizar la PCR de la mutación en los familiares de primer grado o con sospecha de estar afectados.…”
Section: Discussionunclassified
“…This study aimed to find the genetic variants responsible for channelopathies and cardiomyopathies in a sample of Colombian patients. Previously, a study in long QT syndrome in Colombia had been reported (Burgos et al, 2016). That study aimed to evaluate the performance of semiconductor whole‐exome sequencing in a cohort of 21 patients clinically diagnosed with LQTS.…”
Section: Discussionmentioning
confidence: 99%
“…As part of a cohort of LQTS patients [ 25 ], DNA extraction from the patients’ blood leukocytes was carried out with the QIAmp DNA Mini Kit (Qiagen, Hilden, Germany), according to the manufacturer’s instructions. Whole exome sequencing was carried out in collaboration with Macrogen Inc. (Seoul, Korea), as described in the Supplementary Methods section .…”
Section: Methodsmentioning
confidence: 99%